Віртуальний тур як засіб формування позитивного іміджу міста (на прикладі проекту «Віртуальний Луцьк») - Опейда, Людмила Миколаївна; Опейда, Людмила Николаевна; Opeida, Liudmyla H.; Опейда, Артур Русланович; Опейда, Артур Русланович; Opeida, Artur R. (My University, 2016)
Зі стрімким розвитком інноваційно-інформаційних технологій та широким спектром їх застосування, зокрема в туристичній сфері, виникають нові аспекти у формуванні позитивного іміджу міста, області, туристського регіону. Основним засобом на цьому шляху є створення й упровадження віртуальних 3D-турів, які здатні насамперед значно розширити коло потенційних споживачів турпродукту, роблячи доступними туристичні об’єкти для різних категорій населення, а також викликати неабиякий інтерес у потенційних інвесторів не лише туристичної сфери, а й інших галузей господарювання. Due to the rapid development and wide use of the modern innovative and information technologies, particularly in tourism, new opportunities in the formation of the positive image of the city, region or a tourist region arise. The study examines the impact of virtual tourism on the formation of the city’s positive image, as well as the expansion of potential consumers of tourism products and potential investors, not only in the tourism industry but also in the other sectors of economic activity. The aim of the study is to show the contradictions and conflicts in implementing of virtual tours and examine their role in the formation of a positive image of the city (based on «Virtual Lutsk» project). The results of the study show that developed and implemented virtual tours directly influence the formation of the positive image of the city, region, or a tourist region. Moreover, thanks to 3d tours, travels become accessible to different groups of people. The conclusions of the study recommend further research in this area, in particular by asking Internet users about their impressions of the 3d tours of the city or a region and studying of the impact of tourism on the formation of virtual tourist flows, new acquisitions and investments in the development of the city.
Virtual Tour as a Way of Creating of a Positive Image of the City (Based on «Virtual Lutsk» Project)
Keywords: імідж; туристський імідж міста; віртуальний туризм; віртуальний тур; 3D тур; дестинація; інвестиції; image; the tourist image of the city; virtual tourism; virtual tour; 3d tour; destination; investments